2015
DOI: 10.1158/1078-0432.ccr-14-2759
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and Prognostication in Splenic Marginal Zone Lymphoma: Revelations from Deep Sequencing

Abstract: Purpose: Mounting evidence supports the clinical significance of gene mutations and immunogenetic features in common mature B-cell malignancies.Experimental Design: We undertook a detailed characterization of the genetic background of splenic marginal zone lymphoma (SMZL), using targeted resequencing and explored potential clinical implications in a multinational cohort of 175 patients with SMZL.Results: We identified recurrent mutations in TP53 (16%), KLF2 (12%), NOTCH2 (10%), TNFAIP3 (7%), MLL2 (11%), MYD88 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
124
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(132 citation statements)
references
References 40 publications
4
124
3
1
Order By: Relevance
“…Yolanda Campos-Martín, 1 Nerea Martínez, 2 Azahara Martínez-López, 1 Laura Cereceda, 2 Felipe Casado,…”
Section: -35unclassified
“…Yolanda Campos-Martín, 1 Nerea Martínez, 2 Azahara Martínez-López, 1 Laura Cereceda, 2 Felipe Casado,…”
Section: -35unclassified
“…Hodgkin lymphoma was excluded by the absence of Reed–Sternberg cells on bone marrow histology and by flow cytometry. Although genetic testing for NOTCH2 and TP53 was not done in our patient, studies have shown that these gene mutations are independent markers of poor prognosis [6]…”
Section: Discussionmentioning
confidence: 99%
“…In addition, while some genes are biased to certain lymphoma entities, e.g. SF3B1 mutations in CLL, 14,15 KLF2 mutations in SMZL, [16][17][18] ID3 and TCF3 mutations in BL, 19 STAT3 mutations in large granular lymphocyte (LGL) leukemia, 11 and RHOA mutations in angioimmunoblastic T-cell lymphoma (AITL), 20,21 other genes found recurrently mutated, such as genes involved in DNA repair, epigenetic modification and regulation of transcription (Figure 1), can be detected in multiple subtypes (Table 1) and even in other cancer types.…”
Section: Clinical Impact Of Recurrently Mutated Genes On Lymphoma Diamentioning
confidence: 99%
“…Although they have been linked to poor clinical outcome in DLBCL, 35 SMZL 16 and MCL, 36,37 this information does not currently have any impact on treatment decisions or follow-up strategies for the individual lymphoma patient.…”
Section: Genes With Immediate Impact On Treatment Decisionsmentioning
confidence: 99%
See 1 more Smart Citation